Subcutaneous immunoglobulin therapy for refractory skin thickening in rapidly progressive systemic sclerosis: A case report and literature review. Issue 2 (June 2023) - Cacciapaglia, Fabio; Stano, Stefano; Fornaro, Marco; Iannone, Florenzo
The use of immunoglobulin is a therapeutic option with increasing evidence of efficacy for different rheumatologic autoimmune systemic diseases. Some studies concerning immunoglobulin use in systemic sclerosis have been published with encouraging results. We present the case of a young woman diagnosed with rapidly progressive diffuse cutaneous systemic sclerosis, refractory to therapy with methotrexate and rituximab, which presented a relevant skin improvement after one year of subcutaneous immunoglobulin (2 g/kg cumulative monthly dose, refracted in weekly administrations). Furthermore, a narrative literature review of the evidence for alternative treatments with a focus on immunoglobulin use for systemic sclerosis skin involvement was carried out.